Subrata Roy Chowdhury, The Genesis of Bangladesh, A Study in International Legal Norms and Permissive Conscience, Asia Publishing House; Nueva York, 1972. 345 pp. - Devalle, Susana B. C. (Estudios de Asia y África, 1972)
-